Influence of Silica Fume (SF) Content on Passive Film Formation of Steel Reinforcement Inside Hardened Concrete - Marcella Amaral; Isaac Aguiar Oliveira; Diogo Henrique de Bem; Giovana Costa Réus; Gustavo Macioski; Marcelo Miranda Farias; Marcelo Henrique Farias de Medeiros (Corrosion and Materials Degradation)
Corrosion is one of the causes of failure in reinforced concrete structures, and forming a passive film on the steel is essential for protection. Although several studies have looked at passive film formation in concrete pore solutions, few have considered its formation in hardened concrete and the influence of silica fume (SF) in the binder composition. This study aims to evaluate the influence of the SF content on passive film formation time in concrete. Periodic measurements assessed the electrical resistivity and corrosion current density of concrete samples containing 5%, 10%, 15%, and 20% SF. The alkalinity of the mixtures and the kinetics of the pozzolanic reaction were also monitored by XRD and titration tests. The control mixtures exhibited susceptibility to corrosion, regardless of the curing age evaluated. In contrast, the partial replacement of cement with SF accelerated the formation of the passive film on the steel surface, suggesting a delayed onset of corrosion due to modifications in the physical properties of the concrete. Also, the portlandite content and pH can predict passive film formation, with SF significantly accelerating this process.